Implementasi Permainan Tradisional Lompat Tali Pada Anak Usia 5-6 Tahun di TK Gracia Sudiang - Hesty Bela Hiariej, Grace; Akil Musi, Muhammad; Yusri Bachtiar, Muhammad; Rusliana, Faradillah (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to determine the implementation of the traditional jump rope game for children aged 5–6 years at Gracia Sudiang Kindergarten. This study used a qualitative approach with a descriptive type. Data collection techniques were carried out through observation, interviews, and documentation of the principal, teachers, and 15 children aged 5–6 years in classes B.3 and B.4. The results showed that the implementation of the jump rope game in a structured and integrated manner in learning activities was able to improve gross motor skills such as motor coordination, balance, and agility. In addition, children's social-emotional aspects such as the ability to wait for turns, work together, manage emotions, and foster self-confidence also increased. Supporting factors in implementation include teacher involvement, school support, and children's enthusiasm. Meanwhile, inhibiting factors include limited time, weather, and the influence of gadgets. This study concluded that the traditional jump rope game is an effective and contextual learning medium in developing the physical and social skills of early childhood